Investment model of marital commitment among urban dual-earner couples - Juhari, Rumaya; Mohd Arif, Nur Aqilah (Zes Rokman Resources, 2016)
Marital commitment is one of the essential elements that can justify the stability in marital relationship. Marital instability is an outcome of many risk factors in the relationship which may include lack of commitment of one or both partners towards their marriage. Concerns on the increase number of divorce cases in the country leads to the actualization of this study. This paper aims to determine the relationships between satisfaction level, quality of alternatives, investment size and marital commitment among urban dual-earner couples in Malaysia. The study also examines the level of investment model variables amongst the respondents. Data were gathered from a total of 478 married government servants from dual-earner family. Self-administered questionnaire was used for data collection. Along with demographic measure, participants completed a shortened version of the Investment Model Scale (Rusbult, Martz, and Agnew, 1998) to assess commitment, satisfaction, quality of alternatives, and investment size. Bivariate analyses revealed that age, gender, years of marriage, level of satisfaction, quality of alternatives, and investment size were significantly related to relationship commitment. Additionally, satisfaction level, quality of alternative, and investment size were significant predictors of relationship commitment. The results implied that married individuals who are satisfied with their marriage, having low level of alternatives and invested highly in the relationship to have high marital commitment which may lead to signify a good marital relationship. Efforts should be given on strengthening the investment made by each partner in marriage in view of prevention and intervention programs targeting at married couples.